Hohenbergia erecta (Bromeliaceae: Bromelioideae), a New Once-branched Species from Chapada Diamantina, Bahia State, Brazil - Cavalcante, Brayan Paiva; Silva, Kleber Resende; de Souza, Everton Hilo; Versieux, Leonardo M.; Martinelli, Adriana Pinheiro (Tropical plant biology, 2022)
Hohenbergia is one the most diverse genera in Bahia state, and inhabits almost all regions of the state. As a result of ongoing studies on Hohenbergia in Bahia, Brazil, here we describe and illustrate Hohenbergia erecta, endemic to the municipality of Mucugê, at Chapada Diamantina. Hohenbergia erecta differs from its morphologically related, H. catingae, by an elongated tubular rosette (vs short stem with a crateriform rosette), and a once-branched cylindrical inflorescence (vs 2–3-branched pyramidal inflorescence), with branches congested at the apex (vs branches laxly arranged). Due to a small distribution area in the Caatinga forest and based on a spatial analysis we categorized it as Endangered (EN), following the IUCN criteria. Hohenbergia erecta is endemic to the central region of Chapada Diamantina, dominant in the area, where no other known Hohenbergia species have been found sympatrically. It is important, however, that new field expeditions are conducted in the region to observe the richness of the genus at Chapada Diamantina.